FORMULATION AND EVALUATION OF TERBINAFINE HYDROCHLORIDE MICROSPONGE GEL - THAVVA, VEDAVATHI; BARATAM, SRINIVASA RAO (International Journal of Applied Pharmaceutics, 2019)
Objective: The purpose of the present research work was to formulate and evaluate Terbinafine hydrochloride microsponges using quasi emulsion solvent diffusion technique and microsponge gel by using carbopol for controlled release of the drug and consequently avoiding its side effects. Methods: Microsponges containing Terbinafine hydrochloride were obtained successfully with six different drugs: polymer ratios. The formulations were studied for particle size, physical characterization, and in vitro release. Results: A selected THCI microsponge (MS IV) due to its better results when compared to other microsponge formulations was incorporated in different concentrations of carbopol and formulated as gels and evaluated for its pH, viscosity, spreadability, drug content, in vitro release, antifungal activity and in vivo studies. Among the four microsponge gel formulations, THMG II showed better results like pH 6.2, viscosity 3960 cps, spreadability 18.1 g cm/s, drug content of 87.6% and drug release showed fickian release pattern. The antifungal studies showed a zone of inhibition with 15.8 mm when compared to the pure drug, 19.2 mm, marketed formulation 16.0 mm and also showed better antifungal activity on fungal induced guinea pig skin when compared with control. Conclusion: In this study, we found that the controlled release of terbinafine hydrochloride from the microsponge gel reduced side effects and remarkably decreased gel application for fungal treatment.